Conceptual knowledge and argumentation skills of biology students in animal physiology courses - Amin, Astuti Muh; Adiansyah, Romi; Hujjatusnaini, Noor (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2022)
Argumentation facilitates students’ cognitive activities as they construct scientific knowledge. Studies related to the relationship between conceptual knowledge and argumentation skills in biology learning, especially in animal physiology courses, are still rarely carried out. The primary aim of this study was to determine the correlation between students’ mastery of biology concepts and argumentation skills. A correlational research design was employed. The research sample consisted of 106 fourth semester Biology Education students. The students’ mastery of biology concepts and argumentation skills were evaluated using valid and reliable instruments. Conceptual knowledge measured in this study refers to students’ ability to explain their responses to essay tests on cognitive concepts. Besides, this study also assessed students’ ability to participate in scientific debates and compose written arguments based on the Toulmin's Argumentation Pattern (TAP) framework. This study indicates an association between students’ grasp of biology concepts and their argumentation skills in the ADI class. The regression equation derived from the data analysis is y = 0.608x + 39.05 with a reliability value of 0.179. Meanwhile, there is no strong correlation between conceptual knowledge and argumentation skills in RQA, ADI-Integrated RQA, or traditional classes. This can be influenced by a variety of factors, including students’ inability to adapt and adjust rapidly to the steps introduced into the learning models. Improving argumentation quality can be accomplished through the use of active and innovative learning models or strategies.